Determinan kemandirian keuangan daerah: Peran pendapatan asli daerah, tax effort, dan belanja modal di Jawa Tengah (2019–2023) - Dewi Dersanala (Nur Science Institute, 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD), tax effort, and capital expenditure on the level of regional financial independence of regencies/cities in Central Java Province during 2019–2023. This study employed a quantitative approach using secondary data obtained from the Directorate General of Fiscal Balance, Statistics Indonesia, and official local government websites. The sample was selected using a total sampling technique, yielding 175 observations across 35 regencies/cities over five years. The data were analyzed using panel data regression. The stages of analysis included descriptive statistical analysis, model selection tests, classical assumption tests, and hypothesis testing. The results show that PAD and tax effort have a positive, significant effect on regional financial independence. In contrast, capital expenditure has a negative and significant effect on the level of regional financial independence of regencies/cities in Central Java Province. These findings support stewardship theory, which explains that effective regional financial management can improve regional fiscal independence.